(untitled) (Journal of Environmental Science Studies, 2023)
One of the main causes of issues about the today’s situation of technology comes from a big mismatch between the new technology based on quantum mechanics (laws in the micro world) and the old perspective (mechanistic viewpoint in the macro world) for more than a half century. I explain this circumstance and show how to settle this problem by solving the so-called measurement problem of quantum mechanics. These give us a new perspective which unify the laws of macro and micro worlds and bring the current technology into order. To go this way would be to enter by the narrow gate.